Pengaruh Penanaman Modal dalam Negeri (PMDN) dan Penanaman Modal Asing (PMA) terhadap Pertumbuhan Ekonomi di Indonesia - Fadhilah, Asri Nur; Nurlina; Salman; Rizka; Zahrul Fuad (Jurnal Sociohumaniora Kodepena (JSK), 2023)
The purpose of this study was to determine the effect of domestic investment and foreign investment on economic growth in Indonesia simultaneously and partially. This research uses secondary data from 2012-2021 using the Eviews program. The analysis technique used is multiple linear regression. Based on the results of the analysis it is known that domestic investment and foreign investment simultaneously have a significant effect on economic growth in Indonesia. Domestic investment partially has a positive and significant effect on economic growth in Indonesia, foreign investment partially has a positive and insignificant effect on economic growth in Indonesia.